Reduced Estradiol-Induced Vasodilation and Poly-(ADP-Ribose) Polymerase (PARP) Activity in the Aortas of Rats with Experimental Polycystic Ovary Syndrome (PCOS) - Masszi, Gabriella (Public Library of Science, 2013)
Polycystic ovary syndrome (PCOS) is a complex endocrine disorder characterized by hyperandrogenism and insulin resistance, both of which have been connected to atherosclerosis. Indeed, an increased risk of clinical manifestations of arterial vascular diseases has been described in PCOS. On the other hand endothelial dysfunction can be detected early on, before atherosclerosis develops. Thus we assumed that vascular dysfunction is also related directly to the hormonal imbalance rather than to its metabolic consequences. To detect early functional changes, we applied a novel rodent model of PCOS: rats were either sham operated or hyperandrogenism was achieved by implanting subcutaneous pellets of dihydrotestosterone (DHT). After ten weeks, myograph measurements were performed on isolated aortic rings. Previously we described an increased contractility to norepinephrine (NE). Here we found a reduced immediate relaxation to estradiol treatment in pre-contracted aortic rings from hyperandrogenic rats. Although the administration of vitamin D(3) along with DHT reduced responsiveness to NE, it did not restore relaxation to estradiol. Poly-(ADP-ribose) polymerase (PARP) activity was assessed by poly-ADP-ribose immunostaining. Increased PAR staining in ovaries and circulating leukocytes from DHT rats showed enhanced DNA damage, which was reduced by concomitant vitamin D(3) treatment. Surprisingly, PAR staining was reduced in both the endothelium and vascular smooth muscle cells of the aorta rings from hyperandrogenic rats. Thus in the early phase of PCOS, vascular tone is already shifted towards vasoconstriction, characterized by reduced vasorelaxation and vascular dysfunction is concomitant with altered PARP activity. Based on our findings, PARP inhibitors might have a future perspective in restoring metabolic disorders in PCOS.